A Trifunctional Ni–P/Fe–P Collaborated Electrocatalyst Enables Self‐Powered Energy Systems. Issue 22 (22nd May 2022) - Yang, Rui; Zheng, Xiaozhong; Qin, Minkai; Lin, Binbin; Shi, Xiaoyun; Wang, Yong
Abstract: Recently, extensive research efforts have been devoted to drive electrocatalytic water‐splitting for hydrogen generation by electricity or solar cells. However, electricity from power grid and the intermittent property of sunlight inevitably brings about environmental pollution and energy loss. Thus, a novelty energy system for simultaneous generating H2 from solar energy and overcoming the intermittence of sunlight is highly desirable. Herein, a self‐powered energy system with solar energy as the sole input energy is successfully assembled by integrated Zn–air batteries with stable output voltage, solar cells, and water splitting electrolyzer to efficient H2 production. Specially, the Zn–air batteries are charged by the solar cell to store intermitted solar energy as electricity during light reaction. Under unassisted light reaction, the batteries could release electric energy to drive H2 production. Therefore, the aim for simultaneous generating H2 and eliminating the restrictions of intermittent sunlight are realized. The solar‐to‐hydrogen efficiency and solar‐to‐water splitting device efficiency of the self‐powered energy system are up to 4.6% and 5.9%, respectively. This work provides the novel design systems for H2 production and the usage of renewable energy. Abstract : Based on the multifunctional Ni–P/Fe–P collaborated electrocatalyst, the self‐powered energy system is assembled to generate H2 fully powered from solar energy, achieving the energy and substances circulation. Meanwhile, the solar‐to‐hydrogen efficiency and solar‐to‐water splitting device efficiency of this system are up to 4.6% and 5.9%, respectively.